Rural Development with the Help of Artificial Intelligence - Punjeta, Adarsh Singh (International Journal of Computer Sciences and Engineering, 2025)
About seventy percent of the Indian population lives in villages or in rural areas. Even after more than seventy years of Independence the rural India is lagging behind on the developmental index. So for the true of development of India the villages cannot be neglected rather the villages should be given special care. The Government of India is highly concerned for the development of rural India. Now a days technology is playing very important role in almost every walk of life. Accordingly the technology can be the real game changer for the development of rural India. Artificial Intelligence or AI in short, is the future of the modern world and accordingly it has a lot for the development of rural India. This paper deals with the potential of the Artificial Intelligence in the development of rural India